Giardióza psů v chovné stanici - Horejs, R; Koudela, B (Veterinarni medicina, 1994)
Giardia intestinalis is a pathogenic protozoan which infects humans and a wide range of animals including dogs. Giardia infections in dogs have been reported by several authors. Prevalence of Giardia varies widely depending on the detection method, geographic localization, and population studied. The objective of the study reported here was to determine the prevalence of giardiasis in German Shepherd Dogs in a breeding unit. In our trial conducted over 18 months, 28 bitches, 5 adult males and 101 puppies (between 1.5 and 12 months old) were subjected to individual fecal examination for Giardia cysts, coccidial oocysts and helminth ova. Total 494 individual fecal samples were examined by the magnesium sulphate flotation technique (1.30 sp. gr) and Giardia cysts were detected in 36.2% of fecal samples. Giardia cysts were observed in 1 of 29 (3.4%) fecal samples from adult males, 11 of 157 (7.0%) fecal samples from bitches and 164 of 308 (53.2%) puppies' fecal specimens. No association between bouts of diarrhea and peaks of Giardia cysts shedding could be demonstrated. The source of infection for the pups was not ascertained, as no temporal association between shedding of Giardia cyst by bitches and their litters could be demonstrated. The majority of pups had passed peak of Giardia cyst shedding between week 6 of age 12 week of age. When Giardia infection was detected, the dogs were treated with either ornidazole (Avrazor, Léciva) at 25 mg/kg or metronidazole (Entizol, Polfa) 50 mg/kg for three to five days. Within seven days of completing a course of treatment fecal examinations were carried out on each dog to determine whether treatment had been effective.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: psi; Dog Diseases; Female; Animals; Breeding; ženské pohlaví; chov; mužské pohlaví; Dogs; Male; nemoci psů; zvířata; giardiáza; Giardiasis